ANALISIS EFISIENSI DAN FAKTOR YANG MEMENGARUHI PILIHAN SALURAN PEMASARAN - Rizka Karlina Putri; Rita Nurmalina; Burhanuddin Burhanuddin (MIX: Jurnal Ilmiah Manajemen, 2018)
Abstract. This research is intended to analyze the efficiency and the factors influencing the choice of marketing of vanda douglas cutting orchids in Bogor district. Respondents in this study requires 40 farmers vanda douglas cutting orchids. The analysis of marketing channel efficiency uses marketing margins, farmers' share and profit-to-cost ratio. The result of this research is there are three patterns of marketing channel of Vanda douglas cutting orchids: (1) farmers - village collector traders - wholesalers - consumers (2) farmers - wholesalers - consumers (3) farmers - florists - consumers. Seen from the efficiency of the most efficient marketing channel is on channel two that is farmers - wholesalers - consumers. Where on this channel has a low margin of 72 percent, farmer shares by 28 percent and the ratio of profit to the largest cost of 7.4. Of the seven factors that affect the quality of work. Vanda douglas hence significant explanatory variable to response variable is farmer age, orchid sale price, long farming and land area.